Development Status and Trend Forecast of China's Iron and Steel Industry Based on Multi-Algorithm Coupling Modeling - Wang, Tengyu; Ni, Yuting (International Journal of Computer Science and Information Technology, 2024)
Iron and steel metallurgy, as the most important weapon of the country, is ushering in a new round of good opportunities under the support of the national big infrastructure strategy. In this paper, we first use Python to crawl the data, and then use the data visualization software Emotional Sky visualization platform to get the big screen of steel industry data, and analyze the future development of the steel industry through the use of multi-algorithm coupled prediction method. The prediction of the future development of the iron and steel industry is realized through multi-algorithm coupling, and a new round of outlook on the iron and steel industry is proposed based on the prediction. Contribute to the early realization of efficient, intelligent and green development of China's iron and steel industry.